The Effect of Inflation on Economic Growth in Indonesia in Priode 2015-2023 - Mahdy, Salim Imam; Shifa, Mutiara; Safriati, Wahdini; Manan, Afni Abdul (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
This research investigates the effect of inflation on Indonesia's economic growth from 1983 to 2014. This research uses descriptive and econometric analysis. This research carries out econometric analysis using simple linear regression (OLS). The research results show that the independent variable has an effect on the dependent variable with a probability value (F-statistic) lower than α = 5%. The t test results show that the inflation variable influences economic growth with a probability value of 74.7588%, while the remaining 25.2412% is influenced by the independent variable.